Influence of Socioeconomic Status on Stage at Presentation of Laryngeal Cancer in the United States. (11th June 2019) - Lebo, Nicole L.; Khalil, Diana; Balram, Adele; Holland, Margaret; Corsten, Martin; Ted McDonald, James; Johnson‐Obaseki, Stephanie
Abstract : Objective: Identify socioeconomic predictors of stage at diagnosis of laryngeal cancer in the United States. Study Design: Retrospective analysis of the North American Association of Central Cancer Registries' Incidence Data–Cancers in North America Deluxe Analytic File for expanded races. Setting: All centers reporting to the US Centers for Disease Control and Prevention's National Program of Cancer Registries. Subjects and Methods: All cases of laryngeal cancer in adult patients from 2005 to 2013 were reviewed. Ordinal logistic regression models were used to evaluate odd ratios (ORs) for socioeconomic indicators potentially predictive of advancing American Joint Committee on Cancer stage at diagnosis. Results: A total of 72, 472 patients were identified and included. Analysis revealed significant correlation between advanced stage at diagnosis and: Medicaid insurance, lack of insurance, female sex, older age, black race, and certain states of residence. The strongest predictor of advanced stage was lack of insurance (OR, 2.212; P <. 001; 95% CI, 2.035‐2.406). The strongest protective factor was residing in the state of Utah (OR, 0.571; P <. 001; 95% CI, 0.536‐0.609). Once adjusted for regional price and wage disparities, relative income was not a significant predictor of stage at presentation across multiple analyses. Conclusion: Multiple socioeconomic factors were predictive of severity of disease at presentation of laryngeal cancer in the United States. This study demonstrated that insurance type was strongly predictive, whereas relative income had surprisingly little influence.